2007
DOI: 10.1002/chem.200700113
|View full text |Cite
|
Sign up to set email alerts
|

Selective Treatment of Cancer: Synthesis, Biological Evaluation and Structural Elucidation of Novel Analogues of the Antibiotic CC‐1065 and the Duocarmycins

Abstract: Novel diastereomerically pure β‐D‐galactosidic prodrugs (+)‐12 a–e of the cytotoxic antibiotics CC‐1065 and the duocarmycins were prepared for an antibody directed enzyme prodrug therapy (ADEPT) using 4 as a substrate via a radical cyclization to give rac‐5 and rac‐6 followed by a chromatographic resolution of the enantiomers of rac‐5, glycosidation and linkage to the DNA‐binding units 10 a–e. These only slightly toxic compounds can be toxified enzymatically by an antibody–β‐D‐galactosidase conjugate at the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…When tested against the A549 cell line, the galactoside 88a exhibited micro molar activity, but significantly was shown to be more than 5000-fold active in the presence of β-Dgalactosidase (IC 50 = 0.75 nM). In contrast, the (-)-diasteromeric seco-agent showed activity 1000-fold lower than that of (+)-isomer [138,145,146]. Investigation of the role of the sugar moiety found that the identity of this group was important for prodrug stability; after 24 h exposure to culture medium, the prototype galactoside 88a was 72% hydrolyzed, whereas 88b-e were 94-98% intact [141].…”
Section: Adept Strategy Based Prodrugsmentioning
confidence: 97%
See 1 more Smart Citation
“…When tested against the A549 cell line, the galactoside 88a exhibited micro molar activity, but significantly was shown to be more than 5000-fold active in the presence of β-Dgalactosidase (IC 50 = 0.75 nM). In contrast, the (-)-diasteromeric seco-agent showed activity 1000-fold lower than that of (+)-isomer [138,145,146]. Investigation of the role of the sugar moiety found that the identity of this group was important for prodrug stability; after 24 h exposure to culture medium, the prototype galactoside 88a was 72% hydrolyzed, whereas 88b-e were 94-98% intact [141].…”
Section: Adept Strategy Based Prodrugsmentioning
confidence: 97%
“…48) where the phenolic hydroxyl group is protected as glycoside. The N,N-dimethylaminoethoxyindole carboxylic acid component facilitates binding in the DNA minor groove and increases water solubility [137,145]. When tested against the A549 cell line, the galactoside 88a exhibited micro molar activity, but significantly was shown to be more than 5000-fold active in the presence of β-Dgalactosidase (IC 50 = 0.75 nM).…”
Section: Adept Strategy Based Prodrugsmentioning
confidence: 99%
“…As examples we chose three different drug molecules (Fig. 3): raloxifen, a partial agonist of the estrogen receptor; 23,24 ibrutinib, a potent covalent kinase inhibitor (IC 50 of 3–6 nM in chronic active BCR signaling B-cell lymphoma 25 ); and a duocarmycin analog, a highly cytotoxic prodrug of a DNA-alkylating agent with IC 50  < 1 nM in human bronchial carcinoma cells 26 . We prepared drug conjugates by attaching each drug to the pyridinium linker and 5-mer PNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(13A). In alternative, the trichloro-acetimidate of tetraacetyl galactose can be prepared to exploit Schmidt's galactosidation reaction [25,57,58]. Its preparation consists of a reaction between -Dgalactose pentaacetate, previously treated with HClO 4 adsorbed on SiO 2 , and trichloroacetonitrile [68].…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…Drug activation is elicited enzymatically by an antibody--D-galactosidase conjugate at the surface of malignant cells Fig. (6) [57][58].…”
Section: Cancermentioning
confidence: 99%